Peran Perempuan Pesisir dalam Mempromosikan Wisata Bira Melalui Media Sosial - Adha, Riska Aidilia; Yunisa, Yunisa; Muhajir, Abdillah Maulana Islam; Awaru, A. Octamaya Tenri; Khairunniza, Liza Dwi Eftiza (Indo-MathEdu Intellectuals Journal, 2025)
This study aims to analyse the role of coastal women in the Bira area, Bulukumba Regency, in promoting tourism through social media and its impact on the local economy, women's empowerment, and tourism sustainability. The research uses a qualitative method with a case study design. Data was collected through in-depth interviews, participatory observation, and documentation studies, with informants selected purposively based on the criteria of coastal women who actively promote Bira tourism, have resided there for at least one year, and are willing to provide information. Data analysis was conducted through data reduction, data presentation, and thematic conclusion drawing. The results of the study show that coastal women play an important role in producing and disseminating digital content through Instagram and TikTok to increase destination visibility, facilitate accommodation promotion through digital platforms, introduce local cultural identity through products such as woven fabrics, and build tourist attraction through direct interaction with tourists. This role has an impact on increasing MSME income, opening up employment opportunities for women, strengthening digital skills, and preserving local culture. This study recommends strengthening digital literacy training, forming women's business groups, and developing community-based tourism promotion to support women's empowerment and coastal tourism sustainability.